Vitamin D and colon cancer - Klampfer, Lidija (World J Gastrointest Oncol, 2014)
Calcitriol, 1α, 25-dihydroxyvitamin D(3) (1,25 (OH)(2)D(3)), the most active form of vitamin D, is a pleotropic hormone with a wide range of biological activities. Due to its ability to regulate calcium and phosphate metabolism, 1,25D(3) plays a major role in bone health. In addition, 1,25D(3) binds to the vitamin D receptor and thereby regulates the expression of a number of genes which control growth, differentiation and survival of cancer cells. In agreement, the levels of vitamin D(3) appear to be an essential determinant for the development and progression of colon cancer and supplementation with vitamin D(3) is effective in suppressing intestinal tumorigenesis in animal models. Vitamin D(3) has been estimated to lower the incidence of colorectal cancer by 50%, which is consistent with the inverse correlation between dietary vitamin D(3) intake or sunlight exposure and human colorectal cancer. Several studies confirmed that increasing vitamin D(3) lowers colon cancer incidence, reduces polyp recurrence, and that sufficient levels of vitamin D(3) are associated with better overall survival of colon cancer patients. Vitamin D regulates the homeostasis of intestinal epithelium by modulating the oncogenic Wnt signaling pathway and by inhibiting tumor-promoting inflammation. Both activities contribute to the ability of 1,25D(3) to prevent the development and progression of colon cancer.